Strangulated parahiatal hernia to gastric volvulus content - Vázquez, Aníbal; Santandreu, Jorge; Perrone, Luis (Cirugía del Uruguay, 1993)
The author presents a case of strangulated para-hiatal hernia whose content corresponded to an anterior partíal axial mesenteric gastric volvulus which appeared in a 64 year old female.